Crystal Structures of the Global Regulator DasR from Streptomyces coelicolor: Implications for the Allosteric Regulation of GntR/HutC Repressors. - Fillenberg, Simon; Frieß, Mario; Körner, Samuel; Böckmann, Rainer; Muller, Yves (PLoS ONE, 2016)
Small molecule effectors regulate gene transcription in bacteria by altering the DNA-binding affinities of specific repressor proteins. Although the GntR proteins represent a large family of bacterial repressors, only little is known about the allosteric mechanism that enables their function. DasR from Streptomyces coelicolor belongs to the GntR/HutC subfamily and specifically recognises operators termed DasR-responsive elements (dre-sites). Its DNA-binding properties are modulated by phosphorylated sugars. Here, we present several crystal structures of DasR, namely of dimeric full-length DasR in the absence of any effector and of only the effector-binding domain (EBD) of DasR without effector or in complex with glucosamine-6-phosphate (GlcN-6-P) and N-acetylglucosamine-6-phosphate (GlcNAc-6-P). Together with molecular dynamics (MD) simulations and a comparison with other GntR/HutC family members these data allowed for a structural characterisation of the different functional states of DasR. Allostery in DasR and possibly in many other GntR/HutC family members is best described by a conformational selection model. In ligand-free DasR, an increased flexibility in the EBDs enables the attached DNA-binding domains (DBD) to sample a variety of different orientations and among these also a DNA-binding competent conformation. Effector binding to the EBDs of DasR significantly reorganises the atomic structure of the latter. However, rather than locking the orientation of the DBDs, the effector-induced formation of β-strand β* in the DBD-EBD-linker segment merely appears to take the DBDs 'on a shorter leash' thereby impeding the 'downwards' positioning of the DBDs that is necessary for a concerted binding of two DBDs of DasR to operator DNA.

Structural insight into operator dre-sites recognition and effector binding in the GntR/HutC transcription regulator NagR - Fillenberg, Simon; Grau, Florian; Seidel, Gerald; Muller, Yves (Nucleic Acids Research, 2015)
The uptake and metabolism of N-acetylglucosamine (GlcNAc) in Bacillus subtilis is controlled by NagR (formerly named YvoA), a member of the widely-occurring GntR/HutC family of transcription regulators. Upon binding to specific DNA operator sites (dre-sites) NagR blocks the transcription of genes for GlcNAc utilization and interaction of NagR with effectors abrogates gene repression. Here we report crystal structures of NagR in complex with operator DNA and in complex with the putative effector molecules glucosamine-6-phosphate (GlcN-6-P) and N-acetylglucosamine-6-phosphate (GlcNAc-6-P). A comparison of the distinct conformational states suggests that effectors are able to displace the NagR-DNA-binding domains (NagR-DBDs) by almost 70 Å upon binding. In addition, a high-resolution crystal structure of isolated NagR-DBDs in complex with palindromic double-stranded DNA (dsDNA) discloses both the determinants for highly sequence-specific operator dre-site recognition and for the unspecific binding of NagR to dsDNA. Extensive biochemical binding studies investigating the affinities of full-length NagR and isolated NagR-DBDs for either random DNA, dre-site-derived palindromic or naturally occurring non-palindromic dre-site sequences suggest that proper NagR function relies on an effector-induced fine-tuning of the DNA-binding affinities of NagR and not on a complete abrogation of its DNA binding.